2015
DOI: 10.3892/or.2015.4306
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of osteopontin promotes resistance to cisplatin treatment in HCC

Abstract: Osteopontin (OPN) is a multi-functional cytokine involved in cell survival, migration and adhesion. Increasing evidence has elucidated its role in tumorigenesis, progression and metastasis. However, the role of OPN in chemoresistance of human hepatocellular carcinoma (HCC) has not yet been clarified. In the present study, we examined the expression of OPN in human HCC samples before and after cisplatin-treatment, the results showed that OPN was significantly increased in cisplatin-resistant specimens. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
2
13
0
2
Order By: Relevance
“…5,6 Elevated OPN levels participated in many cancers, including breast, prostate, liver, cervical, lung and osteosarcoma. [7][8][9][10][11][12][13] However, the relationship between OPN and cancer stem cells of osteosarcoma is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Elevated OPN levels participated in many cancers, including breast, prostate, liver, cervical, lung and osteosarcoma. [7][8][9][10][11][12][13] However, the relationship between OPN and cancer stem cells of osteosarcoma is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested the involvement of SPP1_v3 in B‐ALL cell survival and related signalling pathways. In accordance, Ding et al () also demonstrated the involvement of SPP1 in resistance to cisplatin in hepatocellular carcinoma cells by activating the PI3K/AKT signalling pathway, while the blockade of SPP1 pathway promoted chemosensitivity in these cells. Additionally, we found that when SPP1_v3 was knocked down in B‐ALL cells, there was also a significant downregulation of CD44 s and CD44 v9 (SPP1 receptors) transcript expression levels (Fig A).…”
supporting
confidence: 65%
“…Osteopontin is a multi-functional cytokine that is involved in cell survival, migration and chemotherapy-resistance, including sorafenib-resistance in patients with metastatic renal cell carcinoma [36, 37]. We also observed that sorafenib upregulated osteopontin expression in human hepatoma cell lines and that c-Jun played a role to some extent in this step (Fig 7).…”
Section: Discussionmentioning
confidence: 60%